(untitled) (Medico Legal Update, 2021)
This study was conducted in the hatchery belonging to Al-Anwar Poultry Company,by injecting the hatching eggs at the age of 17.5 days from the age of the embryos with nano Silver, after that, and raised hatching chicks from the injected eggs in the field of poultry belonging to the Department of Animal Production, College of Agriculture, University of Al-Qasim Green for the period from 6/8/2017 until 9/9/2017, and after that the laboratory work was done, as it used 168 broiler chickens and was reared in cages 1 x 1.5 m, the chicks were randomly divided into seven treatments, and each treatment had three replicates, including each replicate of 8 chicks. Nano-silver was used by injecting it into the eggs in concentrations(0,4,6,8,10,12,14 ppm) for treatments (T1,T2,T3,T4,T5,T6,T7) respectively, The chicks were raised in the field for a period of 35 days, and in this study we reached the following results, a significant excelled (P<0.01) of the T3 treatment in the length and width of the villi in the Jejunum and the excelled of the two treatments T3,T7 in the depth of crypts of Lieberkuhn, and in the ileum there was a significant excelled (P<0.01) for the treatment T2 in the villi length, while the treatment T7 excelled in the villi width and the treatment T5 and T6 treatment was excelled in the crypts depth